Blind Spot for Sedentarism: Redefining the Diseasome of Physical Inactivity in View of Circadian System and the Irisin/BDNF Axis - Zsuga, Judit; More, Csaba E.; Erdei, Tamas; Papp, Csaba; Harsanyi, Szilvia; Gesztelyi, Rudolf (Frontiers in Neurology, 2018)
The term “diseasome of physical inactivity” was coined by Pedersen to explain clustering of chronic diseases linked to physical inactivity. Accordingly, physical inactivity per se contributes to the accumulation of visceral fat, which, generates chronic low-grade systemic inflammation, contributes to emergence of chronic, non-communicable diseases (type 2 diabetes, cardiovascular diseases, colon cancer, postmenopausal breast cancer, dementia, depression). Diversity of these disorders posits the possible involvement of a supraphysiological system. The circadian system is omnipresent in virtually every cell, it enables adaptation to the diurnal environment, by regulating diverse, fundamental processes (metabolism, locomotor activity, sleep-wake cycles etc.). It is hierarchically organized, with the suprachiasmatic nucleus (SCN) being the master clock that entrains to the dark/light cycle and synchronizes subsidiary molecular clocks in the periphery. Insufficient photic entrainment also causes chronic disease evolution. Recent identification of myokines opened new avenues regarding muscle-brain crosstalk. For example, irisin, may enter the central nervous system and induce brain-derived neurotrophic factor (BDNF) production in several brain areas. BDNF assumes significant role in gating light’s influence in the retinohypothalamic synapse, by having a permissive effect on glutamate signal transduction underlying photic entrainment. Here we provide evidence to support the hypothesis that irisin may facilitate photic entrainment of the SCN, via BDNF. By this irisin opens up possible pathways for peripheral non-photic entrainment signals to exert influence on the master clock that is otherwise resistant to these. Furthermore, we suggest that intertwining processes of circadian, redox, inflammatory and myokine systems lay underneath the diseasome of physical inactivity.